Immunomodulatory Effects of Aerobic Training in Obesity - Thomas Nickel; Henner Hanssen; Ingrid Emslander; Verena Drexel; Gernot Hertel; Arno Schmidt-Trucksäss; Claudia Summo; Zeljka Sisic; Marius Lambert; Eva Hoster; Martin Halle; Michael Weis (Mediators of Inflammation)
Introduction. Physical inactivity and obesity are independent risk factors for atherosclerosis. We analyzed the immunomodulatory capacity of 10-week intensified exercise training (ET) in obese and lean athletes. Markers of the innate immune response were investigated in obese (ONE: ET≤40 km/week) and lean athletes (LNE: ET≤40 km/week and LE: ET≥55 km/week). Methods. Circulating dendritic cells (DC) were analyzed by flow-cytometry for BDCA-1/-2-expression. TLR-2/-4/-7 and MyD88 were analyzed by RT-PCR and Western blot. Circulating oxLDL levels were analyzed by ELISA. Results. BDCA-1 expression at baseline was lower in ONE compared to both other groups (ONE 0.15%; LNE 0.27%; LE 0.33%; 𝑃<.05), but significantly increased in ONE after training (+50%; 𝑃<.05). In contrast, BDCA-2 expression at baseline was higher in ONE (ONE 0.25%; LNE 0.11%; LE 0.09%; 𝑃<.05) and decreased in ONE after the 10-week training period (−27%; 𝑃<.05). Gene activations of TLR-4 and TLR-7 with corresponding protein increase were found for all three groups (𝑃<.01/𝑃<.05) compared to pre training. A reduction of oxLDL levels was seen in ONE (−61%; 𝑃<.05). Conclusions. Intensified exercise induces an increase of BDCA-1+ DCs and TLR-4/-7 in obese athletes. We hereby describe new immune modulatory effects, which—through regular aerobic exercise—modulate innate immunity and pro-inflammatory cytokines in obesity.